THE IMPROVEMENT OF OBSERVATION REPORT WRITING SKILL THROUGH THE APPLICATION OF THINK PAIR SHARE LEARNING MODEL - Atika, Widya; Sukarno, Sukarno; Wahyuningsih, Siti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The objective of this research is to improve the observation reports writing skill through Think Pair Share Learning Model on 5th grade students. The subjects of this research are teachers and students of 5th grade. This research is a classroom action research which is conducted in two cycles. The techniques of collecting data which used test, observation, interview, and documentation. The date analysis used is interactive analysis model. Validity of data used content validity and technique triangulation. The result of this research is classical completeness on pre-action is 35%, on cycle I the classical completeness increases to 70% and on cycle II the classical completeness increases to 85%. Based on the results of this research it can be concluded that through the application of Think Pair Share learning model, it can improve the observation reports writing skill 5th grade students.